Creative projects for rust programmers : build interesting projects related to domains such as webassembly, parsing and kernel development - Milanesi, Carlo (Packt Publishing, 2020)
A practical guide to understanding the latest features of the Rust programming language, useful libraries, and frameworks that will help you design and develop interesting projects Key Features Work through projects that will help you build high-performance applications with Rust Delve into concepts such as error handling, memory management, concurrency, generics, and macros with Rust Improve business productivity by choosing the right libraries and frameworks for your applications Book Description Rust is a community-built language that solves pain points present in many other languages, thus improving performance and safety. In this book, you will explore the latest features of Rust by building robust applications across different domains and platforms. The book gets you up and running with high-quality open source libraries and frameworks available in the Rust ecosystem that can help you to develop efficient applications with Rust. You'll learn how to build projects in domains such as data access, RESTful web services, web applications, 2D games for web and desktop, interpreters and compilers, emulators, and Linux Kernel modules. For each of these application types, you'll use frameworks such as Actix, Tera, Yew, Quicksilver, ggez, and nom. This book will not only help you to build on your knowledge of Rust but also help you to choose an appropriate framework for building your project. By the end of this Rust book, you will have learned how to build fast and safe applications with Rust and have the real-world experience you need to advance in your career. What you will learn Access TOML, JSON, and XML files and SQLite, PostgreSQL, and Redis databases Develop a RESTful web service using JSON payloads Create a web application using HTML templates and JavaScript and a frontend web application or web game using WebAssembly Build desktop 2D games Develop an interpreter and a compiler for a programming language Create a machine language emulator Extend the Linux Kernel with loadable modules Who this book is for This Rust programming book is for developers who want to get hands-on experience with implementing their knowledge of Rust programming, and are looking for expert advice on which libraries and frameworks they can adopt to develop software that typically uses the Rust language.